Parental decision-making for circumcision of children aged 6–12 years in China: trends, influencing factors and the role of the media - Wu, Yue; Wei, Yi; Liu, Xiang (Frontiers in Urology, 2025)
ObjectiveThis study investigates the factors influencing Chinese parents’ decision to pursue circumcision for their children aged 6–12 years and analyzes the role of the Internet and media in the popularization of related scientific knowledge.MethodsBased on retrospective data from the National Children’s Regional Medical Single Center from 2015 to 2024, along with a questionnaire survey and literature analysis.ResultsThe study found a significant increase in clinic visits (p = 0.000, r = 0.967) and circumcision procedures (p = 0.003, r = 0.831) among children with phimosis over the past decade. Circumcision is no longer entirely dependent on medical professional advice, but is influenced by a wider range of informational and sociocultural factors. Parents’ trust in online medical information (OR = 6.054, 95% CI 1.027-35.683, p = 0.047) and prolonged exposure to media content recommending surgery (OR = 7.500, 95% CI 1.481-37.974, p = 0.015) were independent risk factors contributing to their decision. In contrast, fear of surgical risk (OR = 0.239, 95% CI 0.059-0.965, p = 0.044), anesthesia, high costs, and long recovery times were key deterrents. Further validation of these independent risk factors revealed that internet and social media platforms (e.g., Baidu, Xiao hongshu, and Shake) had a significant impact on parental decision-making through algorithmic recommendations and emotional content, creating an “opinion dominance effect.”ConclusionThe study reveals the complexity of parental decision-making and emphasizes the need to enhance the dissemination of scientific information to mitigate the impact of misleading content on medical decision-making.